Gospel origins and Christian beginnings in honour of James M. Robinson - Goehring, James E., 1950- (Sonoma, CA Polebridge, 1990)
Includes bibliographical references and indexes.
Keywords: Robinson, James McConkey, -- 1924-; Bible. N.T. Gospels -- criticism, interpretation, etc; Jesus Christ -- history of doctrines -- early church,ca. 30-600.; Bible. N.T. Epistles of Paul -- criticism, interpretation, etc; Christianity -- origins